Evaluasi Usability Aplikasi IPKU (Indonesia Power dalam GenggamanKu) Menggunakan Metode System Usability Scale - Putri, Desmiranda Mentari; Herdiansyah, M. Izman; Sutabri, Tata; Supratman, Edi (STMIK Banjarbaru, 2025)
IPKU is an application developed by PT. PLN Indonesia Power to facilitate employee performance improvement. One of the keys to a company's success is the company's ability to empower its employees at all levels in the company. For this reason, an application is needed that can support work activities that can help employees in terms of improving employee performance. During the use of the application, usability testing has never been carried out. This study aims to assess user satisfaction with the IPKU application and determine factors that need to be improved and enhanced based on user responses. This study uses the System Usability Scale (SUS) method. The System Usability Scale (SUS) method was chosen because in this method the testing is carried out by involving end users, so that the test results will be more in accordance with what the user is facing. Respondents consisted of 88 people. The results of the study showed that the SUS score obtained was 70.02. In terms of Acceptability Ranges, it is included in the